Implikasi Perubahan Undang-Undang TNI Terhadap Struktur Ketatanegaraan Indonesia “Sebuah Kajian Terhadap Pengaruh Dwi Fungsi ABRI” - Afriman Oktavianus; Ricci Otto F Sinabutar; Achmad Bahrul Shafa (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
One of the demands of the 1998 Reformation spirit is the abolition of the Dual Function of ABRI. The presence of the TNI in the civilian realm that is humanist and deliberative for consensus raises various problems because they are educated with doctrines for war and national defense. The phenomenon of ABRI's Dual Function reappeared due to the Revision of Law Number 34 of 2004 concerning TNI. The revision also affects the position of the TNI in the Indonesian State System. This study is to find out how the position of the TNI in the Unitary State of the Republic of Indonesia and how the implications of changes in the TNI Law on the Indonesian constitutional order, as well as provide conclusions and suggestions based on the findings that have been researched. The method used is normative juridical research with descriptive and qualitative approaches through literature study. The results showed that the position of the TNI is in accordance with the mandate of the Constitution, namely as a tool to defend, protect, and maintain the integrity and sovereignty of the state. The occupation of the TNI in the civilian sphere is certainly not in accordance with the mandate of the constitution, especially the rigid TNI approach and one command is considered incompatible with the needs of a humanist society and consensus. In conclusion, the occupation of the TNI is not appropriate in the civilian sphere because they are educated with doctrines for war and national defense. As a result, the presence of the TNI in the civilian sector can cause various problems and incongruities.